Prevalence of Asymptomatic Middle Cranial Fossa Floor Pits and Encephaloceles on MR Imaging - Benson, J.C.; Lane, J.; Geske, J.R.; Gompel, J.V.; Krecke, K.N. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Temporal lobe encephaloceles are increasingly identified and treated as epileptogenic foci. However, there is relatively scant research on the prevalence of asymptomatic encephaloceles. This study set out to describe the frequency of incidental temporal lobe encephaloceles and middle cranial fossa pits.MATERIALS AND METHODS: A retrospective review was completed of high-resolution (≤0.5-mm section thickness) axial T2WI for internal auditory canal protocol imaging. The presence and laterality of middle cranial fossa pits (small bony defects containing CSF) and encephaloceles (brain parenchyma protrusion through osseous defects with or without bony remodeling) were recorded. Electronic medical records of patients with encephaloceles were searched for a history of seizure.RESULTS: A total of 203 patients were included in the final cohort; 106 (52.2%) women. Forty-five (22.2%) patients had middle cranial fossa pits: 14 (31.1%) unilateral on the right, 17 (37.8%) unilateral on the left, and 14 (31.1%) bilateral. Ten (5.0%) patients had ≥1 encephalocele, none of whom had a documented history of seizure in the electronic medical record. No significant difference was noted in the frequency of pits or encephaloceles based on sex (P = .332 and P = .383, respectively) or age (P = .497 and P = .914, respectively).CONCLUSIONS: Incidental middle cranial fossa pits are common findings, and their prevalence is not related to age or sex. Temporal lobe encephaloceles, though rarer, also exist occasionally among asymptomatic patients. Such findings have diagnostic implications for encephaloceles identified during imaging work-up for epilepsy.BHAGbrain herniation into arachnoid granulationsMCFmiddle cranial fossa